The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1165/rcmb.2008-0046oc
|View full text |Cite
|
Sign up to set email alerts
|

The Phagocytosis of Crystalline Silica Particles by Macrophages

Abstract: Silicosis is a chronic lung disease induced by the inhalation of crystalline silica. Exposure of cultured macrophages to crystalline silica leads to cell death; however, the mechanism of cell-particle interaction, the fate of particles, and the cause of death are unknown. Time-lapse imaging shows that mouse macrophages avidly bind particles that settle onto the cell surface and that cells also extend protrusions to capture distant particles. Using confocal optical sectioning, silica particles were shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 44 publications
2
65
0
Order By: Relevance
“…Within AM, the phagosome containing particle(s) fuses with lysosomes in order to attempt to degrade the particle. Consistent with this notion, others and our group have observed silica and ENM, including Multi-walled Carbon Nanotubes (MWCNT) and Titanium Nanobelts (TNB), within phagolysosomal compartments in AM following exposure (Gilberti et al , 2008; Hamilton et al , 2009; Hamilton et al , 2013; Hamilton et al , 2014). Silica, MWCNT, TNB and numerous other nanomaterials are resistant to lysosomal degradation, and consequently, downstream consequences are not fully understood.…”
Section: Introductionsupporting
confidence: 72%
“…Within AM, the phagosome containing particle(s) fuses with lysosomes in order to attempt to degrade the particle. Consistent with this notion, others and our group have observed silica and ENM, including Multi-walled Carbon Nanotubes (MWCNT) and Titanium Nanobelts (TNB), within phagolysosomal compartments in AM following exposure (Gilberti et al , 2008; Hamilton et al , 2009; Hamilton et al , 2013; Hamilton et al , 2014). Silica, MWCNT, TNB and numerous other nanomaterials are resistant to lysosomal degradation, and consequently, downstream consequences are not fully understood.…”
Section: Introductionsupporting
confidence: 72%
“…Among such nanosystems, synthetic amorphous silica (SiO 2 )based nanosystems are the most interesting for two reasons: they are emerging as candidates for nanomedical-biotechnological applications (including the use of SiO 2 as a coat ing agent to protect biofluids and cells from the very toxic action of other NPs, such as quantum dots); and they are widely used in industry as clarifying agents for beverages or additives for paper, rubber and plastics. Although crystalline SiO 2 microparticles are well known to be toxic to cells and strongly proinflammatory in vitro, in animal models and in humans [4,5], a grow ing amount of evidence suggests that amorphous SiO 2 NPs also exert a significant degree of cell damage and toxicological effects [6,7]. Xie et al demonstrated that SiO 2 NPs (20 and 80nm diameter) injected in murine models are preva lently found in lungs, liver and spleen macro phages, but are rarely found in other nonphago cytic tissue cells [8].…”
mentioning
confidence: 99%
“…Eighty percent of these macrophages die within 12 hours. 9 It may be that the phospholipidosis in the lung of silica exposed animals is the result of an interaction between stimulated AMs and fibroblasts to induce phospholipid production by type II cells in an attempt to coat particles and lessen toxicity. 10 In vitro studies show that coating of quartz particles with polyvinylpyridine-N-oxide (PVNO) or aluminum lactate (AL) impairs the ability of the particle to elicit inflammation or generate ROS by neutrophils or AMs.…”
Section: Silica Structure Particle Size and Surface Chemistrymentioning
confidence: 99%